Molecular identification and antimicrobial susceptibility profiles of Klebsiella pneumoniae carrying Extended-Spectrum Beta-Lactamase (ESBL) associated genes in Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
Over the years, Klebsiella pneumoniae especially ESBL-producers type has become a global concern. Frequent reports on resistance reaction to a wide range of available antibiotics have resulted in uncontrolled hospital outbreaks. It is a therapeutic obstacle that must be overcome. This study was conducted to profile the microbiological characterization and antimicrobial resistance of ESBL-producing Klebsiella pneumoniae. The bacteria strain undergoing the biochemical tests and disk-diffusion susceptibility tests, respectively. Additionally, the molecular targeted ESBL-producer genes were established through PCR amplification to distinguish the ?-lactamase type of the ESBL-producing Klebsiella pneumoniae isolates. All isolates were confirmed as ESBL-producing Klebsiella pneumoniae with biochemical characterization of acidic, yellow, rupture medium, positive Urease and Citrate test, and negative Indole test. Following the susceptibility test, the ESBL-producing Klebsiella pneumoniae isolates showed resistance to tested Ciprofloxacin, Ceftriaxone, Trimethoprim, Ampicillin, Nalidixic Acid, and Cephalothin. Lastly, the PCR amplification successfully identified at least one or more ?-lactamase types in all isolates. The identified ?-lactamase consists of TEM, OXA, SHV, CTX-M-1, and CTX-M-9. The presence of at least one or more of the ?-lactamase gene in the Klebsiella strain should be taken seriously by the clinicians as the gene is capable to developed multidrug antibiotic resistance.  Further and additional researches need to be implored to fully understand the capabilities of ESBL-producer type bacteria.
Keywords: Antibiotics; Extended-Spectrum-Beta-Lactamase (ESBL); Klebsiella pneumoniae; Microbiological; PCR Amplification